2009
DOI: 10.1007/s00535-009-0132-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hepatitis C virus replication by chloroquine targeting virus-associated autophagy

Abstract: The results of this study suggest that the replication of HCV replicon utilizes machinery involving cellular autophagic proteolysis. The therapy targeted to autophagic proteolysis by using chloroquine may provide a new therapeutic option against chronic hepatitis C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
95
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 34 publications
(41 reference statements)
1
95
0
4
Order By: Relevance
“…Recent studies indicated that HCV perturbs the autophagic pathway to induce the accumulation of autophagosomes in hepatoma cells (2)(3)(4)(5)(6)(7)(8)(9). Autophagy plays an important role in the removal of damaged organelles and protein aggregates from cells for recycling and is important for maintaining cellular homeostasis.…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies indicated that HCV perturbs the autophagic pathway to induce the accumulation of autophagosomes in hepatoma cells (2)(3)(4)(5)(6)(7)(8)(9). Autophagy plays an important role in the removal of damaged organelles and protein aggregates from cells for recycling and is important for maintaining cellular homeostasis.…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…16). HCV has also been shown to perturb the autophagic pathway to cause the accumulation of autophagosomes (2)(3)(4)(5)(6)(7)(8). This perturbation is mediated by the unfolded protein response, which is activated by endoplasmic reticulum stress (3,4).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11] In vitro, HCV induced autophagosome formation but was not able to enhance autophagic protein degradation suggesting an inefficient fusion between autophagosomes and lysosomes. 2,6 The results of ultrastructural morphometry obtained in the present study could indirectly support this view.…”
Section: Autophagy In Hcv Patients 2713mentioning
confidence: 99%
“…4 Several recent in vitro studies have suggested that the autophagic pathway is involved in HCV replication in cultured cells. [5][6][7][8][9][10][11] However, the relevance of such findings in vivo remains unknown because autophagy has never been assessed in chronic hepatitis C (CHC) patients. 2,4 The aims of the present study were to evaluate the autophagic response in CHC patients, and to identify factors influencing the autophagy level in such patients.…”
mentioning
confidence: 99%